Dimensional model on how familial vulnerability and environmental factors impact transitional age youth psychopathology: The Transition_psy study - Marchini, Simone; Reis, Joana; Ben-Shaool, Ella; Delhaye, Marie; Kornreich, Charles; Nicolis, Hélène; Slama, Hichem; Leys, Christophe; Delvenne, Véronique (Frontiers in Psychiatry, 2023)
Background: Understanding psychopathology in transitional age youth (TAY) requires a complex model, incorporating familial vulnerability and environmental factors. A trans-diagnostic and dimensional approach seems the most appropriate. Transition_psy study aims to assess factors playing a role in TAY psychopathology and to define predictors. Materials and methods: This article presents part of the Transition_psy study results, a case-control observational study. Youth aged 17 years old were recruited between June 2020 and December 2021, from both clinical [clinical population (CP) group] and non-clinical settings [non-clinical population (NCP) group]. Participants completed self-report questionnaires. The primary outcome to assess TAY psychopathology was the Youth-Self Report (YSR). We evaluated care needs with the Health of The Nation Outcome Scales For Children And Adolescents (HoNOSCA-SR) and quality of life with the World Health Organization Quality of Life – BREF (WHOQoL-BREF). Exposure factors included familial vulnerability, childhood and present environmental factors, such as first-degree family history of psychopathology, the Childhood Trauma Questionnaire (CTQ) and the Family Assessment Device (FAD). YSR scores were compared, between groups, according to exposure factors with ANOVA and linear regression. We performed best subsets selection of multivariable analyses based on the Akaike Information Criterion. This study was registered with ClinicalTrials.gov (Identifier: NCT04333797). Results: 220 TAY (CP=106, NCP=114) were included in the study. Participants were aged 17 years old. The majority were female (69.1%), single (96.8%), and born in Belgium (82.3%). Clinical data were all significantly different between groups. YSR scores were found statistically different according to group (p<0.001), first-degree family history of psychopathology (p<0.001), CTQ (p<0.001), and FAD (p<0.001). Predictive dimensional model suggested that TAY psychopathology can be predicted by group, CTQ and FAD. Significant positive correlation was found between YSR and HoNOSCA (rho=0.81) and negative correlation between YSR and physical and psychological health (rho=-0.69 and -0.71, respectively). Conclusion: This study findings allowed to present a predictive dimensional model on TAY psychopathology, including belonging to a clinical population at transitional age, childhood trauma, and family dysfunction. Further research is needed to replicate Transition_psy study results in other samples. The proposed model could be used in clinical practice to improve assessment of TAY psychopathology.